Pembuatan Aplikasi Event Organizer Clover Berbasis Android - Andreanus Agung; Silvia Rostianingsih; Agustinus Noertjahyana (Jurnal Infra, 2015)
Currently the technology is already highly developed. Any activity can be accessed using the Internet. Many jobs that use the Internet as a media campaign, media transactions, even as database storage, include for event organizers. Event organizer is a team that aims to help client organize the event who is too busy to organize the event. Problems in the event organizer, among others in attendance at the event which took place members, data members of the event organizer itself, setting events on the client and scheduling events that will take place.So that event organizers can arrange a better job application is made to handle data members, members scheduling, attendance of members, to the documentation on the website after the event. Applications created using PHP with Eclipse as a programming language. While the database used is MySQL and web server used is Apache.From the results of testing the application, it can be concluded that the application meets the problems in the event organizers, client can choose the package that has been available, or may determine its own form of the desired event, the leader can perform event notifications to the mobile members, and administrators can determine report an event organizer, and can do maintain event.